PENGARUH KUALITAS INFORMASI, ELECTRONIC WORD OF MOUTH DAN PENGALAMAN BELANJA ONLINE TERHADAP MINAT BELI ULANG PRODUK FASHION GEN Z PADA MARKETPLACE SHOPEE DI KABUPATEN SUMBAWA - Laksmi Tsavitri, Lara; Hartini (Publika Citra Media, 2024)
This research aims to examine the influence of information quality, electronic word of mouth, and online shopping experience on interest in repurchasing Gen Z fashion products at the Shopee Marketplace in Sumbawa Regency. This research uses a quantitative method with an associative approach with data collection techniques through distributing questionnaires. The research sample involved 100 respondents, selected using the Paul Leedy formula and the Non Probability Sampling method with a Purposive Sampling approach. Data analysis was carried out using the Statistical Program for Social Science (SPSS) version 26 application. The research results concluded that: 1) The quality of information has a positive effect on repurchase interest. 2) Electronoc word of mouth has a positive effect on repurchase interest. 3) The online shopping experience has a positive effect onrepurchase interest.